Study on mushroom flour and it’s potential for bakery product - Nisha niranjan (International Journal of Multidisciplinary Research and Studies, 2023)
The present investigation entitled “Study on mushroom flour and its potential for bakery product” was carried out at the Research laboratory, ITM University, Gwalior (M.P.). Mushrooms of the Pleurotus genus are commonly known as “oyster mushrooms” and are popularly consumed all over the world. Oyster mushrooms are the second most widely cultivated mushrooms in the world and Turkey. Mushrooms are rich in proteins, minerals, vitamins, nonstarchy carbohydrates, and dietary fibers, and they have quite low cholesterol, calories, and fat content. The highly perishable nature of fresh mushrooms is attributed to their high moisture content (85%–95%) which favors microbial activities, high respiration rate, delicate texture, and high enzymatic activities. Mushrooms cannot be stored for more than 24 h at ambient temperature, while they can be stored for 1 to 2 weeks in refrigerated conditions. Low-temperature storage of mushrooms decreases respiration and transpiration, delays aging, reduce softening, enhances textural firmness, prevents water loss, wilting, and wrinkling, and, thus, extends the shelf life. Bread is one of the most widely consumed food products in the world and bread-making technology is probably one of the oldest technologies known. A lot of work is done on the fortification of wheat flour with high protein materials from plant sources such as legumes to increase the protein and improve the essential amino acid balance of the resultant baked product such as bread has been recognized. Starch is an important ingredient in a range of formulated products, many of which are baked. The experiment was laid out in the Completely Randomized Design with three replications. Each replication was comprised of seven treatments consisting of different concentrations of wheat flour and mushroom flour in bakery products. The result concluded that the treatment T7 (85 % Wheat flour + 15 % Mushroom flour) was found the best treatment of wheat and mushroom flour for making bakery products among all the treatments and it was significantly influenced by the different biochemical, minerals, physicochemical and sensory parameters of bakery products. The maximum bio-chemical, minerals, physicochemical, and sensory parameters were recorded in treatment T7 (85 % Wheat flour + 15 % Mushroom flour), whereas the maximum parameters were observed in treatment T1 (100 % Wheat flour).